Perceptions of institutional influence on the scalability of social enterprise: a study of social entrepreneurial practise in the South African food Industry - Larbi, Lee Calvin Jojo Tete (My University, 2017)
The field of social entrepreneurship is gaining prominence in academic research through its ability to drive innovation and solve complex societal problems. There is a growing interest in this field due to the inherent appeal of entrepreneurship as well as the need to address social inequalities. However, despite the growing interest in social entrepreneurship, there is limited academic research in the subject – especially with regards to the nexus between institutional influence and scale of social enterprise. The majority of social entrepreneurial endeavours in South Africa are found in the food industry. Despite the magnitude of the role that social entrepreneurs play in this industry, research remains limited. Definitional debates with a bias towards conceptual research over empirical research dominates current study on social entrepreneurship – resulting in a lack of consensus among researchers on what social entrepreneurship means. In addition to the above, social entrepreneurship literature has devoted insufficient empirical and theoretical work to the study of scaling of social impact. The majority of the theoretical work has been geared towards the development of practitioner frameworks. The empirical research in the field has also been limited, specifically with regards to understanding the drivers of successful scaling of social entrepreneurial organisations. The majority of these empirical studies have utilised comparative case study approaches. Using institutional theory as a lens, this research aimed to develop a conceptual framework that can be utilised by social entrepreneurs, as well as relevant stakeholders in order to promote the scale of individual social enterprises, particularly in the South African food industry, by developing a “roadmap” to scaling. In addition to the above, the focus was on food security in the South African food industry. It is intended that the conceptual framework can indirectly address the broader societal issues surrounding food security. The above was achieved through a qualitative study. Perceptions of institutional influence on scale as well as start-ups, and drivers of scale were identified through conducting a literature review. A conceptual framework was then established from these constructs. The next step involved conducting semi-structured interviews with 14 social entrepreneurs in the food industry to validate the constructs, and identify the relationships between the constructs. The data was then analysed using the Interpretative Phenomenological approach. The result of the qualitative research is a conceptual research framework, with certain hypotheses. The empirical study identified social innovation as well as the implementation of impactful governmental policies as the most critical institutional influencers of scale. In addition, using SCALERS model as a reference, the empirical study identified lobbying, alliance building, and staffing as drivers to scale. It is noted that that lobbying and alliance building can be linked to government policies as it relates to the collaboration of social enterprises in order to influence policymakers, in addition, staffing relates to the use of volunteers to bring new innovative solutions to the business – these drivers of scale (based on SCALERS model) reinforce the identified institutional influences as critical to scale. If all of the above are present, with all things being equal, then social ventures are more likely to scale – resulting in economic growth and in addition, social issues such as food security will be addressed. From a social entrepreneurship perspective, this study made a substantial contribution in shifting the social entrepreneurship research focus from conceptual, definition biased research towards empirical research that strengthened theoretical research on social entrepreneurship.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce by Research in the field of Management to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, June 2017
Keywords: Social entrepreneurship--South Africa; Food industry and trade--South Africa